2010
DOI: 10.1097/ico.0b013e3181ac4faa
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Keratoconus Associated With Spontaneous Corneal Perforation

Abstract: We present 2 cases of spontaneous corneal perforation in patients with keratoconus. The first patient developed a corneal scleral fistula 1 year after her initial diagnosis of hydrops. We conclude that adequate eye care education, allergy prophylaxis, and fall precautions may be necessary in patients with keratoconus to prevent corneal perforations. Medical and surgical treatments are both viable first-line treatments for corneal perforations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Rubbing or contact lens trauma have a role in hydrops but chiefly the weaker Desçemet's membrane in keratoconus responds to IOP distension 4 . That hydrops is usually associated with rubbing 25 is consistent with trauma due to the associated acute IOP elevation. Hydrops is more common in atopy and Down Syndrome children 4 and both are associated with a higher prevalence of both keratoconus and abnormal rubbing habits 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubbing or contact lens trauma have a role in hydrops but chiefly the weaker Desçemet's membrane in keratoconus responds to IOP distension 4 . That hydrops is usually associated with rubbing 25 is consistent with trauma due to the associated acute IOP elevation. Hydrops is more common in atopy and Down Syndrome children 4 and both are associated with a higher prevalence of both keratoconus and abnormal rubbing habits 26 .…”
Section: Resultsmentioning
confidence: 99%
“…26 Similarly, corneal perforation in hydrops might be associated with even a single incident of rubbing trauma; 25 however, case reports of hydrops and perforation might be associated with a denial of a history of eye rubbing. 25,27 It is possible that a patient's denial of a history of rubbing in such cases could be based on guilt feelings of self harm. Alternatively, undisclosed rubbing might have occurred during sleep or without awareness.…”
Section: Iop Elevation and Plastic Responses Such As Hydrops And Perfmentioning
confidence: 99%
“…6 In cases of corneal perforation in the setting of keratoconus, Stoiber et al 20 reported histological evidence of "fistula" formation. 21 Each of the cases reported here had serological investigations performed to exclude autoimmune associations, and 2 of the 3 patients had corneal swabs to exclude herpetic eye disease. There was no history of trauma immediately before any of the perforations.…”
Section: Discussionmentioning
confidence: 98%
“…Although the exact etiology of corneal hydrops is unclear, it is often associated with progressive ectatic disease, severe allergic eye disease, and habitual eye rubbing [ 2 ]. Rare cases can cause perforation and fistula formation [ 3 ]. In keratoconus patients, the onset of hydrops is generally spontaneous and proportional to the degree of corneal steepening [ 2 ].…”
Section: Discussionmentioning
confidence: 99%